(untitled) (Религиски дијалог и соработка, 2023)
The armed aggression of the Russian Federation, which began in 2014, drew the attention of society and religious institutions to the Armed Forces of Ukraine and revealed problems in the establishing and developing the institution of military chaplaincy. This study aims to assess the basics of spirituality and practice, mission and functions of chaplaincy in the Russian-Ukrainian war. It was found that according to their main credo “Be close!”, military chaplains have become an integral part of the military teams providing spiritual and moral support for military personnel. The activity of military chaplains extends far beyond direct service in military units in the combat zone or their deployment in Ukraine. Military chaplains became volunteers who 1) coordinate and deliver humanitarian aid to the military and civilians, 2) maintain contacts with the families of servicemen, wounded and demobilized soldiers, 3) initiate the creation of special programs of spiritual renewal at monasteries, rehabilitation courses at church communities, social events, etc. The chaplains have shown the readiness to resist the challenges of a new phase of largescale military invasion of Ukraine by the Russian Federation since February 2022. There are no analogies in contemporary history of creating an institute of military chaplaincy under such conditions that makes the current experience of Ukrainian chaplaincy unique.